Association between Lipid Profile and Macro Metals Calcium and Magnesium - Priya Gangadaran1, Mitra Ghosh3, S. Swaminathan1*, Mrudula Wilfred2 (Journal of Experimental Sciences, 2011)
There is a large and rapidly growing body of literature on the importance of calcium and magnesium in biochemical and physiological processes. The objective of this study was to examine the relationship of serum lipid profile to the macro metals calcium and magnesium. Recent findings suggest that both calcium and magnesium play a vital role in many disease states notably in cardiovascular disease. Both calcium and magnesium intake is directly related to cardiovascular disorders. Magnesium acts as a mild calcium antagonist on vascular disease. Prospective studies involving both calcium and magnesium has given inconsistent results. This study done on 50 patients (25 males & females) attending cardiac clinic has shown good correlation between lipid profile and calcium and magnesium suggesting that along with the gold screening test of lipid profile in the diagnosis of cardio vascular disease (CVD), Calcium and magnesium should also be investigated to decide an appropriate supplementation therapy.